Management practices benefit endangered Poweshiek skipperling (Oarisma poweshiek) in Manitoba tall grass prairie - Samantha M. Knight; Barbara I. Bleho; Melissa A. Grantham; Richard Westwood; Nicola Koper; Cary D. Hamel (Canadian Science Publishing, 2024)
Poweshiek skipperling (Oarisma poweshiek Parker, 1870) populations have declined precipitously in the past few decades, and their global range is now restricted to two isolated regions, one of which is the managed Manitoba tall grass prairie in Canada. In this paper, we used a decade of survey data from 2010 to 2019 to understand how habitat features, management practices, and extreme weather impact Poweshiek skipperling abundance in Manitoba. The strongest predictor of abundance was the density of black-eyed Susans (Rudbeckia hirta L.), a primary nectar plant for adults. Poweshiek skipperling abundance also had a negative relationship with both the number of years since a burn occurred and the number of years since grazing occurred. Cumulative precipitation during their active period (May-June) had a negative relationship with skipperling abundance, whereas warm early springs and cool temperatures during the active period had positive relationships. These results suggest that management actions that maintain tall grass prairie habitat in an early successional stage (burning and grazing) and maintain important nectar sources benefit this population. In contrast, extreme weather events had varying effects on Poweshiek skipperling abundance. Results from this study inform ongoing management practices in the Manitoba tall grass prairie to support this endangered population.